2000
DOI: 10.1046/j.1472-4642.2000.00067.x
|View full text |Cite
|
Sign up to set email alerts
|

Species richness of marine Bryozoa in the continental shelf and slope off Argentina (south‐west Atlantic)

Abstract: A total of 246 marine bryozoan species was recorded within an area of the southwest Atlantic between 35° and 56°S, and between the coast of Argentina and 50°W. The distribution pattern of benthic stations surveyed during the most important cruises in the area shows that the sampling effort has been biased towards southern shelf areas off Santa Cruz and Tierra del Fuego, as well as around the Malvinas (Falkland) islands. The littoral zone, Patagonian gulfs and the continental shelf off Chubut, Río Negro and Bue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(22 citation statements)
references
References 21 publications
1
21
0
Order By: Relevance
“…Factors operating at the biogeographic scale, such as a smaller species pool at lower than at higher latitudes off Argentina may be responsible for this pattern. Biogeographic analyses of several macrobenthic groups in the southwestern Atlantic have shown that species richness is higher in the cold-temperate Magellan region than in warm-temperate waters at lower latitudes (Bastida et al 1992, López Gappa 2000, López Gappa et al 2006. Similarly, a review of Chilean benthic nearshore ecosystems suggested that there is a biodiversity hotspot south of 42°S in the southeastern Pacific (Fernández et al 2000, Valdovinos et al 2003.…”
Section: Discussionmentioning
confidence: 99%
“…Factors operating at the biogeographic scale, such as a smaller species pool at lower than at higher latitudes off Argentina may be responsible for this pattern. Biogeographic analyses of several macrobenthic groups in the southwestern Atlantic have shown that species richness is higher in the cold-temperate Magellan region than in warm-temperate waters at lower latitudes (Bastida et al 1992, López Gappa 2000, López Gappa et al 2006. Similarly, a review of Chilean benthic nearshore ecosystems suggested that there is a biodiversity hotspot south of 42°S in the southeastern Pacific (Fernández et al 2000, Valdovinos et al 2003.…”
Section: Discussionmentioning
confidence: 99%
“…The squares were numbered from west to east and from north to south, following a procedure applied for the study of other groups of benthic invertebrates (see López Gappa 2000, López Gappa and Landoni 2005, Montiel et al 2005, López Gappa et al 2006and Genzano et al 2009). …”
Section: Study Areamentioning
confidence: 99%
“…The heterogeneous, poorly sorted facies of the midand outer-shelf were noted by Probert & Wilson (1984) as a possible explanation for the species-rich infaunal assemblages of Otago shelf, given that poorly sorted sediments tend to support richer faunal assemblages (Gray 1974). The richness of ostracod assemblages on Otago shelf was also positively correlated with sediment coarseness and heterogeneity (Swanson 1979), while for the New Zealand region, Rowden et al (2004) found a correlation between heterogeneous bryozoan/molluscan-derived sediments and the diversity of all bryozoans (see also Gappa 2000).…”
Section: Bryozoans As Habitatmentioning
confidence: 99%